2022
DOI: 10.1039/d1qo01871j
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed direct γ-C(sp3)–H arylation of β-alkoxy cyclohexenones: reaction scope and mechanistic insights

Abstract: Direct γ-C(sp3)-arylation of unactivated electron-rich enones is a long-standing challenge. Herein, we report a mild Pd-catalyzed method for direct γ-C(sp3)-arylation of various unactivated β-alkoxy cyclohexenones. The method is not only...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…1-Substituted 6H-indol-6-one (1) 1 (Figure 1) belongs to Nheterobicyclic enone, which is the core skeleton of biologically active benzylphenethylamine-type alkaloids, 2 and widely found in Amaryllidaceae alkaloids, for example, lycorane (1a), lycorine (1b), lycoris (1c), kirkine (1d), fortucine (1e), and others. 3 Due to the important biological activities and the attractive chemical structures of these alkaloids, extensive advances in their total synthesis have been achieved.…”
mentioning
confidence: 99%
“…1-Substituted 6H-indol-6-one (1) 1 (Figure 1) belongs to Nheterobicyclic enone, which is the core skeleton of biologically active benzylphenethylamine-type alkaloids, 2 and widely found in Amaryllidaceae alkaloids, for example, lycorane (1a), lycorine (1b), lycoris (1c), kirkine (1d), fortucine (1e), and others. 3 Due to the important biological activities and the attractive chemical structures of these alkaloids, extensive advances in their total synthesis have been achieved.…”
mentioning
confidence: 99%
“…In 2021, Li-Dong Shao et al 25 reported Pd-catalyzed direct γ-C(sp 3 )-H arylation of β-alkoxy cyclohexenones, and they found the phenomenon that the H on C(γ) was transferred to the C(α') position during the deuterium labeling experiments. Therefore, they launched a DFT mechanism study on the H migration step, only to find that the energy barrier for direct [1,5]-H shift is so high that it is almost impossible to occur under the experimental conditions (Scheme 1c).…”
Section: Resultsmentioning
confidence: 99%
“…23 Recently, On Ying Yuen reported the first ligand control of Pd-catalyzed site-selective αand γ-arylation of α,βunsaturated ketones with aryl halides (Scheme 1b), and Li-Dong Shao reported the Pd-catalyzed γ-arylation of β-alkoxy cyclohexenones (Scheme 1c). 24,25 Through experimental mechanism investigations, they all observed that there was an H shift phenomenon during their reaction, and Shao proposed that it was mainly determined by the tunneling effect. Since α,β-unsaturated ketone (enone) fragments have multiple reaction sites and exist in many biologically active substances, 26,27 the reactions discovered by Yuen and Shao have important theoretical and practical significance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the preliminary toxicity of 1z was also tested using human embryonic kidney cells (293T). 51 As a result, 1z [IC 50 = 32.65 μM, selectivity index (SI) towards MCF-7: ∼4.2] was less toxic than both DDP (IC 50 = 10.81 μM) and GA (IC 50 = 0.53 μM), but more toxic than NB (IC 50 > 100 μM, data not shown) (Fig. S1 †), thereby establishing a foundation for subsequent optimization of this category of HSP90 inhibitors.…”
Section: Rsc Medicinal Chemistry Research Articlementioning
confidence: 99%